2018
DOI: 10.1016/j.pmedr.2018.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Does modified Otago Exercise Program improves balance in older people? A systematic review

Abstract: Exercise interventions focused on strength and balance are effective for falls prevention in older people, however compliance to exercise is often a problem. Tailored intervention programs are recommended to meet the person preferences and increase compliance. Otago Exercise Program (OEP) is the most disseminated fall prevention program and is individually prescribed at home. The purpose of this study was to identify OEP modified formats and investigate their effects on balance when compared to its original fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 48 publications
3
58
0
1
Order By: Relevance
“…Effects pre-to post-treatment in both groups show the effectiveness of the Otago exercise programme on balance, mobility, quality of life and falls independently of whether delivered in the group session or, as usual at home. A recent systematic review including patients aged from 60 to 95 years confirms the effectiveness of the Otago exercise programme in every variation for an improvement in balance and functional ability [56].…”
Section: Main Findingsmentioning
confidence: 88%
“…Effects pre-to post-treatment in both groups show the effectiveness of the Otago exercise programme on balance, mobility, quality of life and falls independently of whether delivered in the group session or, as usual at home. A recent systematic review including patients aged from 60 to 95 years confirms the effectiveness of the Otago exercise programme in every variation for an improvement in balance and functional ability [56].…”
Section: Main Findingsmentioning
confidence: 88%
“…The authors of the review concluded that, in general, all studies using a "modified" OTAGO reported improvements in balance and functional abilities in general. However, whether or not these adapted formats are as effective as the original OTAGO, and which is the most effective, remains unclear, because different adaptations of the OTAGO were applied in different studies [65]. In this sense, more studies are needed to bring greater clarity to this still controversial topic.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise interventions focused on strength and balance are effective for fall prevention in older people 13) . Neuromuscular training is responsible for dynamic joint stability, which is defined as training and enhancing unconscious motor responses by stimulating both afferent signals and central mechanisms 5) .…”
Section: Discussionmentioning
confidence: 99%